Personal or impersonal? : an analysis of Karl Barth and Merrill Unger's perspectives on the personhood of the demonic - MacDonald, Scott Douglas (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.